The effectiveness of computers at the primary school level in Terengganu / Zamri Mohd Noor ... [et al.] - Mohd Noor, Zamri; Abu Bakar, Nordin; Mahmood, Rosman; Abdullah, Rooswadi (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
The advent of computers has affected almost all aspects of society. Computers in education have resulted in an evolution of the education system in the country. Consistent with the effort to realize the vision 2020, the Ministry of Education is planning to introduce computing subjects in secondary schools. This paper discusses the result of the research done to find out the scenario at the primary school level and suggests some computer-related programs to minimize the potential problems when the students take computing subjects in secondary schools.